2003
DOI: 10.1088/1126-6708/2003/02/011
|View full text |Cite
|
Sign up to set email alerts
|

Exact description of D-branes via tachyon condensation

Abstract: We examine the fluctuations around a Dp-brane solution in an unstable D-brane system using boundary states and also boundary string field theory. We show that the fluctuations correctly reproduce the fields on the Dp-brane. Plugging these into the action of the unstable D-brane system, we recover not only the tension and RR charge, but also full effective action of the Dp-brane exactly. Our method works for general unstable D-brane systems and provides a simple proof of D-brane descent/ascent relations under t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
117
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 45 publications
(120 citation statements)
references
References 66 publications
3
117
0
Order By: Relevance
“…Indeed, in [23,24], we showed that the decent relations and the ascent relations exactly, i.e. the equivalences between the boundary state of the unstable Dp-brane system and the one of the BPS Dq-brane.…”
Section: Jhep07(2018)008mentioning
confidence: 97%
See 1 more Smart Citation
“…Indeed, in [23,24], we showed that the decent relations and the ascent relations exactly, i.e. the equivalences between the boundary state of the unstable Dp-brane system and the one of the BPS Dq-brane.…”
Section: Jhep07(2018)008mentioning
confidence: 97%
“…the equivalences between the boundary state of the unstable Dp-brane system and the one of the BPS Dq-brane. Using [23,24], the diagonalization of the tachyon gives the equivalence between the boundary state of the D0-branes and the one of the D2-brane explicitly, where all the string scale l s corrections are included. This method was applied to the Nahm equation [25], ADHM construction of instantons [26], the supertubes [27] and Nahm transformation [28].…”
Section: Jhep07(2018)008mentioning
confidence: 99%
“…For this, it would be more convenient to use following another definition of the conjugate acting trivially on the forms: (dx µ 1 · · · dx µn ) † = (dx µ 1 · · · dx µn ). With this and the non-trivial factor appeared in the transformation from A toÃ, we see that The generalization to the Dp-antiDp brane system can be done following [5,19] with the T-dualized formula. In this system the RR-charges are known to be generated by the ascent relation [57,58] by the tachyon condensation and there would be analogue of this for the massive fields.…”
Section: Jhep03(2015)077mentioning
confidence: 89%
“…Taking this effect into account, instead of (4.11), we will have 12) where * represents the fermionic * -product defined in [19]. Thus, the gauge transformation is given by…”
Section: Jhep03(2015)077mentioning
confidence: 99%
See 1 more Smart Citation